New frontiers in state constitutional law dual enforcement of norms - Gardner, James A., 1959-; Rossi, Jim, 1965- (New York ; Oxford : Oxford University Press, 2011)
Chapters featured in this title include: 'Dual Enforcement of Constitutional Norms', 'Cool Federalism and the Life Cycle of Moral Progress', 'Why Federalism and Constitutional Positivism Don't Mix', and 'Interjurisdictional Enforcement of Rights in a Post-erie World', amongst others.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 10, 2011).
Keywords: Federal government -- United States; Constitutional law -- United States; Judicial review -- United States